The Fifth Pillar of the Balanced Scorecard: Sustainability - VAYVAY, ÖZALP; KALENDER, ZEYNEP TUĞÇE (ELSEVIER SCIENCE BV, 2016)
In today's business environment, sustainability is a trend which can allow companies to implicate social, economic and environmental pillars to the strategy and management of the company. Although the sustainability concept is not new, many organizations still do not know how to implement or measure its outputs. This study aims to look closer to sustainability issue as a fifth pillar of the balanced scorecard which combines financial and nonfinancial issues into a comprehensive performance management system. Balance scorecard was being adopted by companies all over the world to implement corporate strategy, thus it can be considered as a bridge to implement sustainability strategy and link corporate sustainability objectives with actions and performance outcomes. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Balanced scorecard; Sustainability; Strategic management; Sustainable balance scorecard; ENVIRONMENTAL-MANAGEMENT; CORPORATE SUSTAINABILITY; PUBLIC-SECTOR; PERFORMANCE; METHODOLOGY; MODEL